Inactivation mechanisms of non-thermal plasma on microbes: A review - Liao, Xinyu; Liu, Donghong; Xiang, Qisen; Ahn, Juhee; Chen, Shiguo; Ye, Xingqian; Ding, Tian (Food control, 2017)
The increasing consumption of fresh-like food products requires the development of mild processing technologies without loss of nutritional value and sensory quality of foods. Non-thermal plasma (NTP) is an emerging and promising technology for extending the shelf-life of food products. However, the further development of a novel preservation technology should base on the adequate understandings of the effects on microbial behaviors. Therefore, the aim of this review is to provide an overview of the inactivation mechanisms of NTP technology on microbes. Topics covered are the basic introduction of NTP, the intrinsic and extrinsic factors affecting microbial inactivation effect and the probable mechanisms for microbial inactivation. Many factors, including processing parameters, environmental conditions and microbial properties have been shown to influence the bactericidal effect of NTP. According to previous research, the inhibitory activity of NTP against microbes includes biological and physical scenarios, though the exact mechanisms still remain unknown, requiring more investigations in the future. •The intrinsic and extrinsic factors affecting bactericidal efficacy of non-thermal plasma were reviewed.•The probable inactivation mechanisms in biological and physical aspects by non-thermal plasma were summarized.•The non-thermal plasma induced microbial physiological alterations were shown.•The safe application of non-thermal plasma in the future for food industry was proposed.